Allogeneic hematopoietic stem cell transplantation for aplastic anemia with pre‐transplant conditioning using fludarabine, reduced‐dose cyclophosphamide, and low‐dose thymoglobulin: A KSGCT prospective study. Issue 3 (19th December 2019) - Kako, Shinichi; Kanda, Yoshinobu; Onizuka, Makoto; Aotsuka, Nobuyuki; Usuki, Kensuke; Tachibana, Takayoshi; Kobayashi, Takeshi; Kato, Jun; Yano, Shingo; Shimizu, Hiroaki; Shono, Katsuhiro; Tanaka, Masatsugu; et al.
Abstract: The optimal pre‐transplant conditioning for aplastic anemia (AA) remains unclear. We performed a prospective study on allogeneic transplantation from a related or unrelated donor for adult patients with AA. We assessed whether reduced‐dose cyclophosphamide (CY) could decrease toxicity while maintaining engraftment, and low‐dose thymoglobulin could safely prevent graft‐vs‐host disease (GVHD). The pre‐transplant conditioning regimen consisted of fludarabine 120 mg/m 2, CY 100 mg/kg, and thymoglobulin 2.5 mg/kg with or without 2 Gy of total body irradiation. Twenty‐seven patients with a median age of 36 years were analyzed. Sixteen patients received graft from related donors. The stem cell source was bone marrow in 26 patients. All of the patients but one, who died early, achieved neutrophil engraftment at a median of 19 days. Mixed chimerism was observed in six and five patients at days 30 and 90, respectively. Only one patient experienced secondary engraftment failure with complete donor‐type chimerism. None of the patients developed severe acute GVHD. The cumulative incidence of chronic GVHD was 37.7% at 1 year. The overall survival rate was 96.3% at 1 year and 3 years. A high EB virus‐DNA load was detected in one patient at days 60. No one developed EBV‐lymphoproliferative disorder within a year. The results suggest that the conditioning regimen in this study was safe and effective. However, relatively high incidence of chronic GVHD needs further improvement.